Unveiling the South African official primary mathematics teacher pedagogic identity - Peter Pausigere; Mellony Graven (Perspectives in Education, 2013)
This article is theoretically informed by Bernstein’s (2000) notion of pedagogic identity, supplemented by Tyler’s (1999) elaboration of Bernstein’s theory into an analytical framework that describes four possible identity positions relating to classification and framing properties. The article analyses key primary mathematics curriculum policy documents to investigate the official primary mathematics teacher identity as constructed by both previous and current South African education curricula. The article reveals that the first post-apartheid curriculum, Curriculum 2005 (C2005), projected a ‘therapeutic’ primary mathematics teacher identity with symbolic pedagogical intentions. The recent South African curriculum policy changes to a common curriculum framework (Curriculum and Assessment Policy, CAPS) and universal primary learner tests (Annual National Assessments, ANA) construct and promote a ‘market’ (Bernstein 2000) primary mathematics teacher identity.